2017
DOI: 10.1038/srep42355
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of the Ruminococcus flavefaciens FD-1 cellulosome reflects an expansion of family-related protein-protein interactions

Abstract: Protein-protein interactions play a vital role in cellular processes as exemplified by assembly of the intricate multi-enzyme cellulosome complex. Cellulosomes are assembled by selective high-affinity binding of enzyme-borne dockerin modules to repeated cohesin modules of structural proteins termed scaffoldins. Recent sequencing of the fiber-degrading Ruminococcus flavefaciens FD-1 genome revealed a particularly elaborate cellulosome system. In total, 223 dockerin-bearing ORFs potentially involved in celluloso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 63 publications
1
32
0
5
Order By: Relevance
“…Dietary modulation can alter the microbial community and metabolic activity (27, 28). Previous studies showed that many members of the Rikenellaceae, Lachnospiraceae and Ruminococcaceae families show a high potential for fermenting dietary proteins (29-31). Short-chain fatty acids (SCFAs) are important microbial metabolites that serve as important nutrients for the gut epithelium and body tissues that can affect the metabolism, immune response and anti-inflammatory function (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary modulation can alter the microbial community and metabolic activity (27, 28). Previous studies showed that many members of the Rikenellaceae, Lachnospiraceae and Ruminococcaceae families show a high potential for fermenting dietary proteins (29-31). Short-chain fatty acids (SCFAs) are important microbial metabolites that serve as important nutrients for the gut epithelium and body tissues that can affect the metabolism, immune response and anti-inflammatory function (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the cellulose-degrading reputation of F. succinogenes, the detected CAZymes were predominately involved in soluble glucans and/or hemicellulose degradation (Figure 2), with representatives belonging to the family of GH11, GH51 and GH94 amongst the most abundant glycoside hydrolases. In addition to F. succinogenes, R. albus and R. flavefaciens have also been repeatedly shown to contribute many of the required CAZymes for biomass-degradation in the rumen 36,[40][41][42] . Indeed, endoglucanase GH9, a CAZyme family capable of hydrolyzing β 1→ 4 glyosidic bonds in cellulose, were detected in the proteome of both R. albus and R.…”
Section: Metaproteome-generated Cazyme Profile Indicates Compartmentamentioning
confidence: 99%
“…Some of the most efficient biomass degrading anaerobes possess cellulosomes, which are multienzyme complexes that enable the orchestrated and synchronized activity of various enzymes that are needed to degrade the cellulosic and hemicellulosic components of recalcitrant plant material 48 . Until recently, cellulosomes and their essential building blocks have been identified and described only from anaerobic bacteria 40,[49][50][51] . However, advances in the isolation and cultivation of anaerobic fungi coupled with genome and transcriptome analyses have confirmed the presence of cellulosomes in anaerobic fungi for the wellsynchronized deconstruction of plant carbohydrates 4 .…”
Section: High Prevalence Of Multi-modular Domains and Cellulosomal Prmentioning
confidence: 99%
“…Essa ampla variação motivou a subsequente divisão das dockerinas de tipo-III em seis grupos e onze subgrupos, que serão discutidos em maiores detalhes abaixo. 1,14 No grupo 6, temos homólogas de algumas dockerinas de Clostridium e Ruminococcus.…”
Section: Cohesinas E Dockerinas: Os Componentes Centrais Do Celulossomounclassified
“…O subgrupo 6b apresenta o menor linker, com 32 resíduos. 1,14 Outras 8 sequências não se encaixaram em nenhum grupo, por baixa similaridade. Há…”
Section: Celulossomo De Ruminococcus Flavefaciensunclassified